Cellulolytic and Xylanolytic Microbial Communities Associated With Lignocellulose-Rich Wheat Straw Degradation in Anaerobic Digestion - Jensen, Mads Borgbjerg; de Jonge, Nadieh; Dolriis, Maja Duus; Kragelund, Caroline; Fischer, Christian Holst; Eskesen, Martin Rosenørn; Noer, Karoline; Møller, Henrik Bjarne; Ottosen, Lars Ditlev Mørck; Nielsen, Jeppe Lund; Kofoed, Michael Vedel Wegener (Frontiers in Microbiology, 2021)
The enzymatic hydrolysis of lignocellulosic polymers is generally considered the rate-limiting step to methane production in anaerobic digestion of lignocellulosic biomass. The present study aimed to investigate how the hydrolytic microbial communities of three different types of anaerobic digesters adapted to lignocellulose-rich wheat straw in continuous stirred tank reactors operated for 134 days. Cellulase and xylanase activities were monitored weekly using fluorescently-labeled model substrates and the enzymatic profiles were correlated with changes in microbial community compositions based on 16S rRNA gene amplicon sequencing to identify key species involved in lignocellulose degradation. The enzymatic activity profiles and microbial community changes revealed reactor-specific adaption of phylogenetically different hydrolytic communities. The enzymatic activities correlated significantly with changes in specific taxonomic groups, including representatives of Ruminiclostridium, Caldicoprobacter, Ruminofilibacter, Ruminococcaceae, Treponema, and Clostridia order MBA03, all of which have been linked to cellulolytic and xylanolytic activity in the literature. By identifying microorganisms with similar development as the cellulase and xylanase activities, the proposed correlation method constitutes a promising approach for deciphering essential cellulolytic and xylanolytic microbial groups for anaerobic digestion of lignocellulosic biomass.